THE OUTCOMES OF JOB SATISFACTION ON PUBLIC SECTOR ORGANIZATIONS’ EMPLOYEES ACROSS COUNTRIES: A SYSTEMATIC REVIEW - Putra, Zainal; Ma’ruf, Jasman J; Yunus, Mukhlis; Harmen, Hamdi (Pattimura University, 2023)
Background: Organizational leaders in public sector organizations must pay serious attention to employee job satisfaction because they provide community services. Ensuring employee job satisfaction in public entities is the key to improving service quality and maintaining their consistency in serving the community. Employees who are satisfied with their work will be willing to work hard to achieve organizational goals. Objectives: We aim to systematically review the empirical literature on employee job satisfaction outcomes in public sector organizations across countries. Design: We conducted a systematic review based on previous researchers’ protocols. Data sources: We use electronic databases, including Scopus Search, PubMed Search, Sciencedirect.com Search, and Google Scholar Search from 2010 to February 2022. Review methods: We include articles that examine the outcomes of employee job satisfaction in public sector organizations. The team independently reviewed and determined each study that met the inclusion criteria. Next, the rest of the team assessed the quality of the papers using a predetermined quality assessment instrument. Then to the included studies, data extraction was carried out. Finally, we conducted an in-depth content analysis to identify the outcomes of employee job satisfaction. Results: We have identified 33 outcomes of job satisfaction. We divided these outcomes into six categories: job attitude, performance, happiness, prosocial behavior, work motivation, and customer satisfaction. The team also found inconsistent research results, providing research gaps for other researchers to follow up